Próba reorganizacji siatki parafii rzymskokatolickich w Lublinie w latach 1864-1866 - Rożek, Jakub (Archiwa, Biblioteki i Muzea Kościelne, 2016)
The Church performs its task of leading people to salvation, among others, through organizing chaplaincy in parishes. It means that parishes are extremely important centres of each diocese and the community of the faithful. It was the same in Lublin in the 1960s. Due to the fact that there were only two parishes in the city, the pastoral work of diocesan priests was also supported by religious orders. However, the tsarist government, in November 1864, dissolved most of the monasteries in the Kingdom of Poland, which caused difficulties in providing appropriate pastoral care. Therefore, at the end of 1864, the then administrator of the Diocese of Lublin Rev. Kazimierz Sosnowski made an attempt to reorganize a parish life in Lublin in order to satisfy religious needs of the faithful and fill the gap left by the dissolved monasteries. The reorganization involved creating two new parishes in the churches which had belonged to the Capuchins and Bernardines before their dissolution and transferring a parish service from St Nicholas Church to St Agnes Church, which had been in the possession of the Augustinians before the dissolution. In order to conduct this project, Rev. Sosnowski started negotiations with the Government Commission of Internal Affairs and Clergy, which finally ended in 1866. This article details the various stages of these negotiations, their causes and effects.